Combined effect of cold joint and yielded hoop reinforcement on cyclic behaviour of seismically detailed RC beam-column joints. (February 2022) - Hussain Choudhury, Arshad; Islam Laskar, Aminul
Abstract: In removal and replacement technique of rehabilitation for reinforced concrete (RC) structures, fragmented concrete from damaged beam-column joints core is removed only and is replaced by suitable high strength repair material. Due to removal and replacement, there exist cold joints between old concrete and new repair material. Moreover, when seismically detailed beam-column joints are subjected to cyclic loading, hoop reinforcements may yield. Such yielded hoops remain inside the repaired joint core after rehabilitation adopting removal and replacement technique. Till date, no attempt has been made to investigate combined effect of cold joint and yielded hoop reinforcement on cyclic behaviour of seismically detailed beam-column joint. When tested under cyclic loading, specimens with both cold joint and yielded hoop reinforcement showcased the highest reduction in cyclic performance in terms of initial stiffness, stiffness degradation, ductility and cumulative energy dissipation compared to individual effect of either cold joints or pre-yielded hoops. Between individual parameters – cold joint and yielded hoop reinforcement, cold joint played a more dominant role. This was established by reduced cyclic performance of specimens with cold joint in terms of initial stiffness (15–17% lower), displacement ductility (7 – 9% lower) and energy dissipation (18 – 19% lower) in comparison to specimens with yielded hoops.